A possible culprit for refractory angina - Nature Research (16552612) (2015)
A large proportion of patients with refractory angina have elevated levels of lipoprotein(a), according to new research published in the Qscience journal Global Cardiology Science & Practice. The new findings suggest that elevated lipoprotein(a) levels may play a causative role in the condition, and that reducing levels of this lipoprotein could be a viable therapeutic option for the patients. Angina occurs when cholesterol plaques are deposited in the coronary arteries, causing a shortage in blood supply to the heart itself. It is said to be refractory when patients continue to experience it after having medical and surgical treatment. Tina Z. Khan of Harefield Hospital in London, UK, and her colleagues conducted a screening pilot study of 75 patients with refractory angina, recruited from cardiology outpatient clinics in the UK. The researchers took blood samples from them and measured levels and distribution of lipoprotein(a), triglycerides, and LDL cholesterol (the harmful type of cholesterol). They then asked them about the presence of cardiovascular risk factors such as diabetes, hypertension, and smoking history. The researchers found that 60% of these patients had raised lipoprotein(a) levels of 500 mg l−1 or higher. Of these, 73% had a family history of coronary heart disease, and 64% also had hypertension. This may implicate lipoprotein(a) as having a causal role in refractory angina, but the findings still need to be confirmed by testing a control group of patients who have coronary heart disease but not refractory angina. An increased lipoprotein(a) level is known to be highly heritable, and is believed to promote hardening of the arteries by trapping cholesterol in the inner linings of blood vessels, promoting clot formation, recruiting inflammatory cells, or binding pro-inflammatory phospholipids. “Conventional cholesterol-lowering medication and adjustments to diet have little to no effect on lowering lipoprotein(a),” says Khan. “The only effective treatment currently available is a dialysis-type treatment called apheresis, which physically removes undesirable cholesterols from the blood, but it is still unclear whether lowering lipoprotein(a) levels could be of therapeutic benefit to refractory angina patients.” Khan and her colleagues are, however, in the process of conducting a randomized, controlled crossover trial in 20 refractory angina patients to examine the clinical and symptomatic impact of apheresis therapy, and expect the results to be available by the end of the year. Other Information Published in: QScience.com Highlights, Published by Nature Research for Hamad bin Khalifa University Press (HBKU Press) License:http://creativecommons.org/licenses/by/4.0